Pengaruh Disiplin Kerja dan Motivasi Terhadap Kinerja Pegawai Pada Badan Pengembangan Sumber Daya Manusia Daerah (BPSDMD) Provinsi Banten - Saifu (Fakultas Ekonomi dan Bisnis Universitas Prima Graha, 2021)
The lack of implementation of employee performance in carrying out tasks so that work is not immediately resolved in compiling reports based on their responsibilities, currently there are still employees who arrive late when they come to work. This study aims to determine: 1. The Effect of Work Discipline on Employee Performance, 2. The Effect of Motivation on Employee Performance, 3. The Effect of Work Discipline and Motivation on Employee Performance at the Office of the Regional Human Resources Development Agency (BPSDMD) Banten Province. The type method in this study uses an associative quantitative method which is causality, which is a study to determine the relationship / influence of independent variables on the dependent variable without making additional changes or manipulation of existing data. The population and sample used in this study were employees of the Banten Province Regional Human Resources Development Agency (BPSDMD), totaling 82 employees. The sampling technique in this study uses a saturated sample where the population is less than <100 employees. The results of this study indicate that: 1. There is a positive and significant effect of Work Discipline on Employee Performance. 2. There is a positive and significant influence of Motivation on Employee Performance. 3. There is a positive and significant influence of Work Discipline and Motivation together on Employee Performance at the Regional Human Resources Development Agency (BPSDMD) Banten Province.